2013
DOI: 10.1515/cclm-2012-0664
|View full text |Cite
|
Sign up to set email alerts
|

A combined index of cardiac biomarkers as a risk factor for early cardiovascular mortality in hemodialysis patients

Abstract: A combined index of cardiovascular risk factors could provide supplementary risk stratification in HD patients for early cardiovascular mortality, strongly supporting the annual routine determination of these biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
6
1
Order By: Relevance
“…Recently, an update of ACC/AHA guidelines stated that the use of myocardial fibrosis biomarkers such as sST2 might be considered for predicting risk of hospitalization and death in patients with chronic HF and potentially added to natriuretic peptide biomarker levels in their prognostic value [ 34 ]. Our study confirms that hs-cTnT, CRP, and to a lesser extent NT-proBNP alone are predictive of poor outcome, as described in a hemodialysis population [ 38 ]. Yet, sST2 alone does not allow CV events or death composite outcome prognosis in nondialyzed CKD patients.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, an update of ACC/AHA guidelines stated that the use of myocardial fibrosis biomarkers such as sST2 might be considered for predicting risk of hospitalization and death in patients with chronic HF and potentially added to natriuretic peptide biomarker levels in their prognostic value [ 34 ]. Our study confirms that hs-cTnT, CRP, and to a lesser extent NT-proBNP alone are predictive of poor outcome, as described in a hemodialysis population [ 38 ]. Yet, sST2 alone does not allow CV events or death composite outcome prognosis in nondialyzed CKD patients.…”
Section: Discussionsupporting
confidence: 90%
“…The combined index of cardiovascular risk factors could supply additional information about cardiovascular mortality in HD patients (32). However, in our study there was no correlation between the cardiac biomarkers.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Necontrasting
confidence: 63%
“…25-29 Furthermore, research thus far has generated conflicting results. Recently, Bargnoux et al 25 suggested that a combination of TnI, NT-proBNP, and CRP levels possibly improved risk assessment for short-term (<2 years) mortality in 140 HD patients. In their study, BNP and CRP were independent predictors of mortality but not TnI, probably because of the small study population.…”
Section: Previous Multimarker Studiesmentioning
confidence: 99%